2021
DOI: 10.2355/isijinternational.isijint-2020-688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Impeller and Gas Stirring on Agglomeration Behavior of Polydisperse Fine Particles in Liquid

Abstract: Agglomeration, coalescence and flotation of non-metallic inclusions in steel melt are effective for obtaining "clean steel." In this study, the agglomeration and breakup behaviors of particles with a primary particle size distribution (hereinafter, polydisperse particles) in a liquid under impeller and gas stirring were compared by numerical calculations and model experiments. The particle-size-grouping (PSG) method in the numerical agglomeration model of particles was combined with a breakup term of agglomera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In the experiment, the agglomeration of particles directly impacts the PSD [28][29][30]. Traditional algorithms, such as concave point detection and watershed methods, can detect the existing agglomerates, but the information is lost during the segmentation process.…”
Section: Image Processing Resultsmentioning
confidence: 99%
“…In the experiment, the agglomeration of particles directly impacts the PSD [28][29][30]. Traditional algorithms, such as concave point detection and watershed methods, can detect the existing agglomerates, but the information is lost during the segmentation process.…”
Section: Image Processing Resultsmentioning
confidence: 99%
“…According to visual observations and previous papers, the sites of fine particle agglomeration, breakup, and transfer in a dual liquid phase are estimated as schematically illustrated in Figure 3. Turbulent agglomeration [9][10][11][12][13][14][15][16] occurs at sites I for hydrophobic particles and I' for hydrophilic ones. Sites I and I' were distinguished because the agglomeration rate of the hydrophobic particles was larger than that of the hydrophilic ones.…”
Section: Ps Particle Floating In Water-oil Interfacementioning
confidence: 99%
“…A simultaneous agglomeration model of two kinds of inclusion was developed and numerically calculated to simulate Al 2 O 3 and slag particles, [11][12][13] and an agglomeration of inclusions with wide particle size distribution was analyzed by a Particle-Size-Grouping (PSG) method. [14,15] Sumitomo et al [16] compared the agglomeration of monodisperse particles between impeller and gas stirring practices, and indicated that the agglomeration rate of the gas stirring was smaller than that of the impeller stirring due to breakup of some agglomerated particles induced by bubble bursting on the gas/liquid-free surface. Fruengieri et al [17,18] simulated the aggregation and breakup of colloidal particles under the effect of a shear field by combining a Monte Carlo algorithm and the discrete element method (DEM).…”
Section: Introductionmentioning
confidence: 99%
“…Yamaguchi et al 14) performed a water model experiment to investigate the agglomeration and breakup behaviors of particles under impeller and gas stirring and compared the results with those of the numerical model.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the agglomeration coefficient has been set to a constant value based on a fitting parameter 15)-16) or an approximate expression 2), 11) in previous studies. Although Nakaoka et al 11) and Yamaguchi et al 14) conducted water model experiments for agglomeration using polydispersed particles as model inclusions, they used a constant agglomeration coefficient for model calculations. Consequently, model calculations using a constant agglomeration coefficient may contain discrepancies when compared to measured values, such as number density and size distribution, among others.…”
Section: Introductionmentioning
confidence: 99%